2017
DOI: 10.1002/anie.201612599
|View full text |Cite
|
Sign up to set email alerts
|

Regiocontrolled Direct C−H Arylation of Indoles at the C4 and C5 Positions

Abstract: An effective and practical strategy has been established for the direct and site-selective arylation of indoles at the C4 and C5 positions with the aid of a readily accessible, cheap, and removable pivaloyl directing group at the C3 position. This transformation shows good functional-group tolerance and could serve as a powerful synthetic tool for the synthesis of medicinally relevant compounds. This method and those developed in previous research together enable the regiocontrolled direct arylation of indole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(72 citation statements)
references
References 71 publications
1
70
0
1
Order By: Relevance
“…The developed catalytic system overrides the ortho‐directing effect as well as electronic biases at the indole C‐2, C‐3 and C‐7 position, mostly due to the sterically hindered N−P(O) t Bu 2 directing group. The authors also demonstrated the C‐5 arylation of indoles using different reaction protocols under the copper catalysis (Scheme ) …”
Section: Arylation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed catalytic system overrides the ortho‐directing effect as well as electronic biases at the indole C‐2, C‐3 and C‐7 position, mostly due to the sterically hindered N−P(O) t Bu 2 directing group. The authors also demonstrated the C‐5 arylation of indoles using different reaction protocols under the copper catalysis (Scheme ) …”
Section: Arylation Reactionsmentioning
confidence: 99%
“…The authors also demonstrated the C-5 arylation of indoles using different reaction protocols under the copper catalysis (Scheme 8). [25] The arylation of indoles is also well documented by the use of 4d metal catalysts like palladium, [26] rhodium, [27] ruthenium [28] Thearylation by these metals showed the excellent regiocontrol at mild reaction conditions compared to the 3d transition metals. Though the catalysts loading is almost similar, the employment of mild conditions is beneficial with the 4d metal catalysts.…”
Section: Cu-catalyzed Reactionsmentioning
confidence: 99%
“…It has become apowerful tool to realize the selective functionalization of the challenging C4-C7 positions of indoles,w hich is assisted by adirecting group in two complementary directions (e.g.,D G 1 and DG 2 ). [7] However,t his strategy cannot be extended to the substitution-pattern tuneable synthesis of benzofuran, because the oxygen atom of benzofuran cannot serve as "anchor donor" for directing group introduction, leaving the remote C6 and C7 sites almost inaccessible.T he second strategy proceeds via annulation, which capitalizes on individual construction of the benzene or five-membered heteroarenes (Scheme 2b:a nnulation). As for the synthesis of benzofuran, mostly pericyclic reactions [8] and transition metal-catalyzed cyclizations [9] were applied to forge the benzene moiety.F or comparison, more studies have been devoted to the construction of the furan moiety by formal [3+ +2] [10] cycloadditions or intramolecular ring-closure reactions [11] with prefunctionalized phenols, [10d-p,11i-m] quinones, [10b,c] or phenolic ethers as starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the direct arylation of indoles at all positions have been achieved, while there are little reports on the diarylation of indoles and their derivatives . Based on our previous work,, , , the investigators were intrigued to determine whether the site‐selective diarylation of indoles could occur. Herein, we report a Pd‐catalyzed strategy for the direct diarylation of 6,7‐benzindoles at the C4 and C5 positions by installing a pivaloyl directing group at the C3 position.…”
Section: Introductionmentioning
confidence: 99%